(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies is an infectious disease caused by a virus belonging to the family Lissavirus that affects all mammals including humans. Rabies transmission occurs by virus-containing saliva , through biting or licking of an injured tissue. The virus replicates at the site of inoculation until it reaches the nerve endings. At the neuromuscular junctions, the virus binds specifically to the nicotinic acetylcholine receptor. On the other hand, alkaloids have yielded interesting results in terms of drug development. Since rabies virus infection is, at least, partially associated to the nicotinic acetylcholine receptor, the present study focus on the evaluation of molecules obtained from the skin secretion of Ameerega picta, in the process of penetration and infection of rabies virus in Baby Hamster Kidney (BKK-21) cells. The secretion was collected though stimulation by manual compression of the amphibian glands, and then separated into 14 fractions by reversed-phase high performance liquid chromatography (RP-HPLC). The fractions were characterized by mass spectrometry and tested for their cytotoxic effect on BHK- 21 cells. Fraction 3 was the only one presenting cytotoxicity, by means of arising morphological changes when compared to the negative control (cells + MEM) and the positive control (cells + 20% DMSO). Subsequently, the fractions were screened for their ability to interfere in the process of virus cellular penetration. The rapid test for inhibition of fluorescent foci (RFFIT) showed that fractions 3, 6 and 7 were able to decrease the viral infection. Analyses by mass spectrometry showed that the molecules present in the active fractions ranged from 200 to 500 Da, which is in the alkaloid molecular mass range. Molecules are undergoing purification for proper virological assays and structural characterization.